Sustainability, Profitability and Added Value Moderated by Company Value on Stock Returns Sri-Kehati Index - Desmita, Desmita; Sihombing, Pardomuan (Asean International Journal of Business, 2024)
This research aims to determine the effect of Sustainability, Profitability and Value Added which are moderated by Company Value on Stock Returns. In this research, sustainability is proxied by environmental, social & governance (ESG), profitability is proxied by return on assets (ROA) while added value is proxied by economic added value (EVA) and market added value (MVA). The population in this research is the Sri-Kehati Index which is listed on the Indonesia Stock Exchange (BEI) in 2018-2022. The sampling technique used in this research was purposive sampling. The sample in this research consisted of 19 companies. This research use a panel data analysis technique with moderated regression analysis (MRA) in E-views 12. The results of this research show that environmental, social & governance (ESG), market value added (MVA) have no influence on stock returns. Meanwhile, return on assets (ROA), economic value added (EVA) and company value have a positive effect on stock returns. Company value weakens the influence of ROA and EVA on stock returns, and company value strengthens the influence of MVA on stock returns.